PENGEMBANGAN MEDIA PEMBELAJARAN ULAR TANGGA KEANEKARAGAMAN HAYATI (ULTAKA) UNTUK MENINGKATKAN MOTIVASI BELAJAR SISWA KELAS VII MTs NEGERI 2 KOTA KEDIRI - Auliyaur Rohmah, Sayyidah; Wenie Ananda Pramudiea Margarieta (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The urgency of this research arises from the need to address the low learning motivation in science (IPA) among Grade VII F students at MTs Negeri 2 Kota Kediri. By developing a learning media called UTAKA (Ular Tangga Keanekaragaman Hayati or Biodiversity Snakes and Ladders), it is expected that a more engaging, interactive, and contextual learning atmosphere can be created, thereby enhancing students’ motivation and understanding of science material. This research is also intended to serve as a reference for the development of innovative instructional media in other schools, particularly in efforts to integrate biodiversity values into the learning process. Based on this background, the purpose of this study is stated in the title: "The Development of Biodiversity Snakes and Ladders (UTAKA) Learning Media to Improve Learning Motivation of Grade VII F Students at MTs Negeri 2 Kota Kediri." This study uses the Research and Development (R&D) method, with the ADDIE development model. The instruments employed include validation questionnaires for media and content experts, student response questionnaires, and learning interest and motivation questionnaires. The data analysis techniques used in this study are percentage-based analysis and the N-gain test. The validation results from the first content expert showed an average score of 97% (categorized as "feasible"), and from the second expert 88% (categorized as "feasible"). Based on the N-gain score of 0.72, which falls into the "high" category (g > 0.7), it can be concluded that the ULTAKA media is effective in increasing students’ learning motivation in science classes.